Neurodevelopmental Characterization of Young Children Diagnosed with Niemann-Pick Disease, Type C1. Issue 5 (June 2020) - Thurm, Audrey; Chlebowski, Colby; Joseph, Lisa; Farmer, Cristan; Adedipe, Dee; Weiss, Madison; Wiggs, Edythe; Farhat, Nicole; Bianconi, Simona; Berry-Kravis, Elizabeth; Porter, Forbes D.
ABSTRACT: Objective: Niemann-Pick disease type C1 (NPC1) is a lysosomal storage disease characterized by progressive neurodegeneration, with the age of diagnosis ranging from the prenatal period through adulthood. Although neurological symptoms usually precede genetic diagnosis, they do not necessarily prompt diagnosis in the early years. Few prospective data are available to describe neurological onset, including neurodevelopmental delays, in children with NPC1. This dearth of information hinders the planning and implementation of adequate monitoring and treatment for the neurodevelopmental sequelae of NPC1. Method: Twenty-nine infants, toddlers, and preschoolers younger than 6 years participated in a natural history study and were administered neurodevelopmental assessments using instruments commonly used for early intervention screening in the community. Results: Twenty-two of 29 participants met the criteria for a significant delay of at least 1.5 SDs below the mean in at least one domain of development; the youngest children often met these criteria for a significant delay based on motor delays, but cognitive and language delays were also common. However, only 11 of the 22 participants were reported to receive early intervention services before study entry. Conclusion: Although neurological symptoms may not prompt the genetic diagnosis of NPC1, the current findings support the use of a multimethod approach to repeated assessments for young children with the diagnosis because of the frequency of developmental delays or decline in multiple domains. The diagnosis of NPC1 alone should qualify children for evaluation for early intervention services and consideration of investigational therapeutic interventions.